The clinical pattern of intentional injuries at a primary Saudi Arabian trauma center - Bader Hamza Shirah; Hamza Asaad Shirah; Ibrahim Abdulaziz Zabeery; Osama Abdulqader Sogair; Ahmed Medawi Alahmari; Wael Awad Alhaidari; Maher Hamdan Alamri; Waal Nafa Aljabri (Journal of Trauma and Injury)
Purpose The term “intentional injuries” refers to a spectrum of injuries resulting from self-inflicted injuries, interpersonal violence, and group acts of violence. Intentional injuries are underreported in Saudi Arabia. This study aimed to analyze and evaluate the characteristics of intentional injuries in patients who presented to the emergency department of a primary trauma center in Medina, Saudi Arabia in 2013. Methods A prospective cohort database analysis of the clinical patterns and treatment outcomes of 252 patients who had intentional injuries between January and December 2013 was done. Results The proportion of trauma patients with intentional injuries was 1.3%. The mean age was 34.2±9.4 years, 141 patients (56.0%) were male, and 111 (44.1%) were female (male to female ratio, 1.27:1). The majority (n=159, 63.1%) of injuries occurred at night. Most occurred outside the home (n=180, 71.0%). Financial problems (n=62, 24.6%) and social disputes (n=61, 24.2%) were the most common reasons. Sharp objects (n=93, 36.9%) were the most common weapons used. The head and neck were the most commonly injured areas (n=63, 54.4%). Superficial cuts (n=87, 34.5%), were the most common type of injury. Suturing of wounds (n=54, 21.4%) and surgical debridement (n=47, 18.7%) were the most commonly performed modalities of management. Conclusions We conclude that intentional injuries in Saudi Arabia are a health care hazard that is, unfortunately, underreported. The clinical pattern is similar in most aspects to international reports but differs in certain features due to the specific religious and conservative characteristics of the community. Nationwide clinical studies are strongly recommended.